EXTENT OF IMPLEMENTATION OF EXTERNAL SUPERVISION FEEDBACK FOR QUALITY ASSURANCE IN SECONDARY SCHOOLS IN ABIA STATE. (UNIZIK Journal of Educational Management and Policy, 2024)
The study was conducted to determine the extent of implementation of external supervision feedback for quality assurance in secondary schools in Abia State. The study was guided by four research questions and four hypotheses. The study adopted descriptive survey research design. The population of the study comprised of 4917 staff. The sample size for the study comprised of 1804 respondents, consisting of 1334 teachers, 454 principals and 16 zonal supervisors in the three education zones in Abia State. The instrument for data collection was self-structured instrument titled ‘‘Implementation of External Supervision Feedback Questionnaire (IESFQ)". It was duly validated by three experts who are lecturers in the Faculty of Education, Nnamdi Azikiwe University. A reliability index of 0.88 was ascertained using Cronbach Alpha. Out of the 1,804 copies of the instrument administered, 1581 copies were duly completed, retrieved and used for data analysis. Data were analyzed using mean and standard deviation for answering the research questions and ANOVA for research hypotheses. The findings revealed among others that external supervision feedback regarding teaching and learning process, leadership and management, teacher quality and school physical environment in secondary schools in Abia State are implemented to a high extent. The study also found out that there is a significant difference in the mean ratings of principals, teachers and supervisors on the extent of implementation of external supervision feedback regarding school leadership and management, teacher quality and school physical environment. Based on the findings of the study it was recommended among others that Secondary Education Management Board should organize seminars, workshops and conferences for secondary school teachers to improve instruction, and ultimately outcome for students in Abia State. Conclusions were drawn; implications of the findings and suggestions for further studies were also made.
Keywords: Implementation, Supervision, Feedback, Quality Assurance, Secondary Education